2006
DOI: 10.1002/ceat.200500354
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy – A Powerful Tool for the Quantitative Determination of the Composition of Polymorph Mixtures: Application to CaCO3 Polymorph Mixtures

Abstract: Raman spectroscopy is an ideal method for identifying polymorphs, because it provides excellent fingerprint spectra specific to each crystal structure. Currently, Raman spectroscopy is successfully used forthe quantitative polymorphic analysis of calcium carbonate only in the case of binary mixtures. When a third polymorph is present in the mixture, errors in the quantitative determination increase due to the difficulty in discriminating the different phases in the Raman spectra. In the present work, a new met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 10 publications
6
67
0
3
Order By: Relevance
“…Calcite is characterised by peaks at 711 cm À1 (4) and 1085 cm À1 (1) and vaterite by a doublet peak at 1088 cm À1 (1). 27 The ratio of calcite to vaterite crystals was approximately 1:1 for all concentrations studied.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Calcite is characterised by peaks at 711 cm À1 (4) and 1085 cm À1 (1) and vaterite by a doublet peak at 1088 cm À1 (1). 27 The ratio of calcite to vaterite crystals was approximately 1:1 for all concentrations studied.…”
Section: Resultsmentioning
confidence: 84%
“…Isolation of the crystals and examination at higher magnification showed that each comprised intergrown rhombohedra (Figure 4(b)), while Raman microscopy of individual crystals confirmed the calcite polymorph through observation of bands at 711 cm À1 (4), 1085 cm À1 (1), and 281 cm À1 (lattice mode vibrations) (Figure 4(c)). 27 In contrast, when calcium carbonate was precipitated by combination of 8 mM CaCl 2 and Na 2 CO 3 solutions within similar sized droplets, only spherical particles 3-4 lm in diameter were produced ( Figure 5). The presence of a narrow double peak at 1088 cm À1 (1) and a broad peak at 302 cm À1 (corresponding to the translational and rotational lattice modes) confirmed the vaterite polymorph.…”
Section: Resultsmentioning
confidence: 99%
“…More recently the IR and Raman spectra have been used as an analytical tool by chemists and mineralogists to separate the carbonate polymorphs: calcite, aragonite, and vaterite. [8][9][10][11][12] Although the vibrational spectra of aragonite have been previously measured, the assignment of the normal modes is incomplete; moreover, no IR data are available in the farinfrared range, and the dielectric function in the far-and midinfrared ranges is still unknown. This is probably due to both difficulties in obtaining a well-characterized single crystal of sufficient optical quality and the absence of accurate references from simulation, two ingredients that constitute novelty elements of the present investigation.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] However, a complete characterization of all spectral peaks, in terms of both frequency and intensity, is rarely performed; the attribution of spectral features to specific modes remains a hard task, too. Previous simulations on the vibrational properties of carbonates have mainly focused on methodological aspects, 17 on the effect of cation substitutions on the infrared spectra, 18 and on the role of the vibrational contributions to the relative stability of polymorphs.…”
mentioning
confidence: 99%